Role of en-APTAS Membranes in Enhancing the NO2 Gas-Sensing Characteristics of Carbon Nanotube/ZnO-Based Memristor Gas Sensors - Ibtisam Ahmad; Mohsin Ali; Hee-Dong Kim (Biosensors)
NO2 is a toxic gas that can damage the lungs with prolonged exposure and contribute to health conditions, such as asthma in children. Detecting NO2 is therefore crucial for maintaining a healthy environment. Carbon nanotubes (CNTs) are promising materials for NO2 gas sensors due to their excellent electronic properties and high adsorption energy for NO2 molecules. However, conventional CNT-based sensors face challenges, including low responses at room temperature (RT) and slow recovery times. This study introduces a memristor-based NO2 gas sensor comprising CNT/ZnO/ITO decorated with an N-[3-(trimethoxysilyl)propyl] ethylene diamine (en-APTAS) membrane to enhance room-temperature-sensing performance. The amine groups in the en-APTAS membrane increase adsorption sites and boost charge transfer interactions between NO2 and the CNT surface. This modification improves the sensor’s response by 60% at 20 ppm compared to the undecorated counterpart. However, the high adsorption energy of NO2 slows the recovery process. To overcome this, a pulse-recovery method was implemented, applying a −2.5 V pulse with a 1 ms width, enabling the sensor to return to its baseline within 1 ms. These findings highlight the effectiveness of en-APTAS decoration and pulse-recovery techniques in improving the sensitivity, response, and recovery of CNT-based gas sensors.